1980
DOI: 10.1002/kin.550121206
|View full text |Cite
|
Sign up to set email alerts
|

Mutual interactions of the methyl and methylperoxy radicals studied by flash photolysis and kinetic spectroscopy

Abstract: The decadic extinction coefficient of the methyl radical at 216.4 nm and the rate constant for mutual combination were redetermined as:The application of the Beer-Lambert law to these measurements was justified experimentally. The absorption spectrum of the methylperoxy radical was characterized as a weak, broad, structureless band, having a maximum at 240 nm with ~(240) = 1.55 X lo3 l./mol cm. The mutual interaction of methylperoxy radicals leads to the generation of methoxy and hydroperoxy radicals as a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 38 publications
(42 reference statements)
2
11
0
Order By: Relevance
“…248 nm (with values around 1.2 × 10 −18 cm 2 ), part of the spectrum extends from 300 nm until about 349 nm. Our results agree reasonably with the experimental measurements of photolysis at least for C 2 H 5 O 2 , for which many studies have found a peak located around 240 nm, with values of 3-5 × 10 −18 cm 2 [15,[17][18][19][20][21][22][23][24][25][26][27][28]. Thus, our model works well for the photolysis cross-section estimation for polyatomic molecules.…”
Section: Photolysis Of Peroxyl Radicals In Ultraviolet Regionsupporting
confidence: 89%
“…248 nm (with values around 1.2 × 10 −18 cm 2 ), part of the spectrum extends from 300 nm until about 349 nm. Our results agree reasonably with the experimental measurements of photolysis at least for C 2 H 5 O 2 , for which many studies have found a peak located around 240 nm, with values of 3-5 × 10 −18 cm 2 [15,[17][18][19][20][21][22][23][24][25][26][27][28]. Thus, our model works well for the photolysis cross-section estimation for polyatomic molecules.…”
Section: Photolysis Of Peroxyl Radicals In Ultraviolet Regionsupporting
confidence: 89%
“…4 ) = 9.8 X lo3 L/mol-cm and ~~~( 2 1 6 . 4 ) = 9.5 X lo3 L/mol.cm [5] Close agreement exists between the values of the rate constants for mutual interaction k? and k y .…”
Section: Resultssupporting
confidence: 56%
“…The relationship between these maxima has prevented the characterization of the acetyl radical spectrum by the flash photolysis of acetaldehyde, which has been shown to generate both acetyl and formyl radicals [l]. In contrast, the maxima of the spectra of the hydroperoxy and methylperoxy radicals are described by the values ~HOO(210) = 1.2 X lo3 L/mol.cm [17] and ~~~~0 0 ( 2 4 0 ) = 1.5 X lo" L/mol.cm [5], and this relationship does not preclude the use of the absorbance of the methylperoxy radical to study its fast reactions in the presence of the hydroperoxy radical Corroborative spectra have been derived for the acetyl radical from the study of the flash photolysis of both methyl ethyl ketone and biacetyl. Values of A40(A) were measured for each system under conditions analogous to those used for the acetone system, and are shown in Figures 7 and 8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations